Synopsis of the project "Development of Professional Courses in Sustainable Water Management" - RESONATE Project - Taneva-Veshoska, Angelina; Ilijovski, Zlatko; Tomik, Ana; Likar-Dimishkovska, Djjana; Mendes, Maria Paula; García Mata, Carolina; Ristić Vakanjac, Vesna; Polomcic, Dusan; Bajic, Dragoljub (Spisanie na b Lgarskoto Geologichesko Druzhestov-Review of the Bulgarian Geological Society, 2021)
The project “Development of Professional Cours-es in Sustainable Water management” (acronym RESONATE) is a two-year project, from October 1, 2019 to September 30, 2021. It is funded by Er-asmus+. The aim of the RESONATE Project is to provide comprehensive engineering knowledge and develop professionals’ scientific, communication and problem solving skills through a combination of hands-on courses, industry projects and theo-retical background.
Keywords: project; sustainable water management; professional courses; online courses; Emerging